2017
DOI: 10.5946/ce.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy Tube Insertion in Neurodegenerative Disease: A Retrospective Study and Literature Review

Abstract: Background/AimsWith the notable exceptions of dementia, stroke, and motor neuron disease, relatively little is known about the safety and utility of percutaneous endoscopic gastrostomy (PEG) tube insertion in patients with neurodegenerative disease. We aimed to determine the safety and utility of PEG feeding in the context of neurodegenerative disease and to complete a literature review in order to identify whether particular factors need to be considered to improve safety and outcome.MethodsA retrospective ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 30 publications
2
40
0
1
Order By: Relevance
“…A further two studies demonstrated a correlation between ALS progression rate and impaired MSC function [25] , [26] , reporting that functional deficiencies in MSCs were proportional to disease progression. Moreover, MSC impaired functionality was also observed in multiple sclerosis (MS) patients [27] . In detail, conditioned media from MSCs of patients with long duration of progressive disease showed reduced neuroglial protective capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A further two studies demonstrated a correlation between ALS progression rate and impaired MSC function [25] , [26] , reporting that functional deficiencies in MSCs were proportional to disease progression. Moreover, MSC impaired functionality was also observed in multiple sclerosis (MS) patients [27] . In detail, conditioned media from MSCs of patients with long duration of progressive disease showed reduced neuroglial protective capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia results in significant morbidity by interfering with medication administration, nutrition and fluid intake, and is associated with aspiration pneumonia -the most frequent cause of death in patients with PS [2] . For PS patients presenting with dysphagia, the decision regarding gastrostomy tube insertion (GTI) for feeding is challenging since to date, few studies have addressed the procedural risks and outcomes in this patient population [3][4] . In contrast, there are already established recommendations for GTI to maintain nutritional support in patients with amyotrophic lateral sclerosis (ALS) that present with severe dysphagia.…”
Section: Maroismentioning
confidence: 99%
“…Parenteral nutrition is generally not preferred in such cases due to a number of shortcomings including the associated metabolic disorders, high cost, difficulty of application, as well as patient comfort. Enteral nutrition, as well as enteral feeding with PEG, are recommended in patients with chronic neurologic conditions such as head trauma, cerebral palsy, neuromuscular disorders, and motor neuron disorders (4,5,6,7,8,9,13,16,17,18,19). In a study by Tokunaga et al (19), 75.3% of their patients with PEG procedures were reported to have cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%